Do Female–Owned Employment Agencies Mitigate Discrimination and Expand Opportunity for Women? - Jennifer Hunt; Carolyn Moehling (Institute of Labor Economics (IZA), 2024)
We create a dataset of 14,000 hand–coded help–wanted advertisements placed by employment agencies in three U.S. newspapers in 1950 and 1960, a time when help–wanted advertisements were divided into male and female sections, and collect information on agency ownership. We find that female–owned agencies specialized in vacancies for women, thereby expanding the access of female jobseekers to agency services, including for positions in majority–male occupations. Female–owned agencies advertised more skilled occupations to women than did male–owned agencies, leading to a 5.5% higher wage for women. On the other hand, female–owned agencies had a greater propensity to match male jobseekers to clerical jobs, contributing to 21% lower male wages than for male–owned agencies. The results are consistent with female proprietors having had a comparative advantage in female jobseekers and clerical occupations or with client firms having trusted female proprietors only with vacancies for women and homogeneous, lower–skill occupations. However, in choosing to establish an agency and to specialize in female jobseekers, female proprietors may have sought to mitigate employer discrimination against female jobseekers; their higher propensity to advertise majority–male occupations among professional, technical and managerial advertisements for women may also reflect discrimination mitigation.
Keywords: N12; J63; J16; 330; job matching; discrimination; gender; employment agencies